Medievalist Enlightenment : from Charles Perrault to Jean-Jacques Rousseau - Montoya, Alicia C. (Medievalism., 2013)
Alicia Montoya shows how, in order to understand the aesthetic and intellectual transformations that marked modernity, it is essential to examine how this period conceived of the past, and particularly those 'Dark Ages' that served as the defining foil for the modern Age of Light.